“They Would Have Stopped Births, if They Only Could have”: Short-and Long-Term Impacts of the COVID-19 Pandemic—a Case Study From Bologna, Italy - Benaglia, Brenda; Canzini, Daniela (Frontiers in Sociology, 2021)
This article addresses the short-term impacts of the COVID-19 pandemic in Italy and hints at its potential long-term effects. Though many might want it to, birth does not stop during a pandemic. In emergency times, birth practices need to be adjusted to safeguard the health of birthing mothers, babies, birth providers, and the general population. In Bologna, Italy, one of the emergency measures employed by local hospitals in response to COVID-19 was to suspend women’s right to be accompanied by a person of their choice for the whole duration of labor and childbirth. In this work, we look at how this measure was disputed by the local activist birth community. Through the analysis of a social campaign empowered by Voci di Nascita—an association of parents, birth providers, and activists—we examine how social actors negotiated the balance between public health and reproductive rights in a time of crisis. We argue that this process unveils several structural issues that characterize maternity care at the local and national levels, including the (re)medicalization of birth, the discourse on risk and safety, the internal fragmentation of Italian midwifery, and the fragility of reproductive rights. The Covidian experience forced the reshaping of the birth carepath during the peak of the emergency. We suggest that it also offered an opportunity to rethink how birth is conceived, experienced, and accompanied in times of unprecedented global uncertainty—and beyond.